PENILAIAN DAYA TARIK OBJEK WISATA ALAM AIR TERJUN GURUNG SEPANGIN DI DESA TEKUDAK KECAMATAN KALIS KABUPATEN KAPUAS HULU - Sarma Siahaan; yohanes bobbie yanter; Siti Latifah (Forestry Study Program University Of Mataram, 2023)
Â Assessment of the attractiveness of natural attractions is a systematic and balanced process or activity to gather information about everything unique, of high attractive value for tourists who come to a tourist destination area. This research is expected to be included in the local government as a consideration in the framework of the management and development of natural attractions. The purpose of the research is to get the value of the attraction of natural attractions of Gurung Sepangin Waterfall. The research was conducted for approximately 3 weeks effectively in the field. The method used is a survey method with interview techniques and assisted by questionnaires as data collection instruments, sampling is carried out accidental sampling based on criteria that have been determined by researchers. The number of respondents was 30 people. Data processing uses guidelines for analysis of object operations and natural attractions (ADO-OTDWA) directorate general of PHKA in 2003 which has been modified according to the scores that have been determined for each criterion. The results of research on the assessment of natural attraction objects of Gurung Sepangin Waterfall have an area attraction value of 954.18 or entered into the classification category (B) means that it is quite potential to be developed into a natural tourist destination.